Optimizing Mass Rearing of the Egg Parasitoid, Telenomus podisi, for Control of the Brown Stink Bug, Euschistus heros - Parra, Letícia Martins [UNESP]; Carvalho, José Romário de; Hoback, William Wyatt; Oliveira, Regiane Cristina de [UNESP] (MDPI, 2023)
The parasitoid Telenomus podisi Ashmead, 1893 is used in biological control programs in Brazil against eggs of Euschistus heros (Fabricius, 1798), a key pest of soybean, Glycine max (L.) Merr. To optimize the mass production of parasitoids, artificial diets and storage of host eggs at low temperatures have been developed; however, direct comparisons of the effects of these conditions have not occurred. We assessed a double factorial arrangement composed of six treatments (fresh or cryopreserved E. heros eggs from adults fed on natural or two artificial diets). We evaluated the biological characteristics and parasitism capacity of T. podisi produced from these treatments across seven temperatures. The thermal range between 21 and 30 °C resulted in satisfactory daily parasitism in all treatments tested, with an inverse relationship between temperature and female survival. The best parasitoid biological parameters were found between 21 and 27 °C, where all tested diets supported T. podisi development, with the best results from artificial diets. Fresh eggs and those frozen in liquid nitrogen and stored at −196 °C until use supported parasitoid development. These results suggest that the best method to mass rear T. podisi is to use artificial diets to rear E. heros and store eggs until needed, and then rear parasitoids at 24 °C.
Keywords: biological control; mass rearing; optimization; parasitoids; stink bug